Unveiling the role of oxidative treatments on the electrochemical performance of carbon nanotube-based cotton textile supercapacitors. (October 2021) - Costa, Rui S.; Soares, O. Salomé G.P.; Vilarinho, Rui; Moreira, J. Agostinho; Pereira, M. Fernando R.; Pereira, André; Pereira, Clara
Highlights: MWCNTs oxidized with HNO3, H2 SO4 or HNO3 /H2 SO4 as supercapacitor electrode materials. Highest S BET and optimum surface oxygen loading on CNTs achieved through HNO3 oxidation. Enhanced energy performance of textile SCs based on oxidized CNTs vs. parent CNTs. 106% energy density improvement for the TSC based on the HNO3 -oxidized CNTs. Redox-active oxygen groups at MWCNTs surface induced pseudocapacitive features. Abstract: Herein, all-solid-state textile supercapacitors (TSCs) were produced using a cost-effective readily-available natural fabric as substrate (cotton) and different types of oxidized multiwalled carbon nanotubes (MWCNTs) as electrode nanomaterials. The MWCNT oxidative treatments were performed using three agents, HNO3, H2 SO4 and HNO3 /H2 SO4, to unveil their role on the performance and energy storage mechanism of the resulting TSCs. The TSCs based on the oxidized MWCNTs exhibited up to 106% enhanced energy density than the device based on pristine MWCNTs (up to 3.48 W h kg −1 vs. 1.69 W h kg −1 ) and up to 98% capacitance retention over 5000 cycles. A balance between the extent of oxidation of the MWCNTs, their specific surface area and electrical conductivity was required to boost the performance. The MWCNT oxidation with HNO3 promoted the highest increase of the specific surface area, the creation of redox-active surface oxygen-based groups and optimum surface oxygen loading (4.0%). The synergy between these features endowed a pseudocapacitive contribution to the energy storage mechanism, leading to the TSC with the best performance. This work constitutes a breakthrough on the rational design of easily scalable TSCs directly produced on natural non-conductive substrates using tuned oxidized MWCNT electrode nanomaterials to meet the demands of the thriving Era of wearable electronics. Graphical abstract: Image, graphical abstract